2022
DOI: 10.1002/cpdd.1090
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Daprodustat and Metabolites in Individuals with Normal and Impaired Hepatic Function

Abstract: Daprodustat is a hypoxia‐inducible factor‐prolyl hydroxylase inhibitor in development for treatment of anemia of chronic kidney disease. We evaluated the role of hepatic impairment on daprodustat pharmacokinetics, pharmacodynamics, and tolerability. Participants with mild (Child‐Pugh Class A, score 5‒6) and moderate (Child‐Pugh Class B, score 7‒9) hepatic impairment and matched healthy controls were administered single 6‐mg doses of daprodustat. Exposure parameters were determined for daprodustat and its six m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Plasma daprodustat data were collected as previously described 17,19 and calculated via standard noncompartmental analysis with WinNonlin 6.3 or higher (Certara, Princeton, NJ). All calculations were based on actual sampling times.…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma daprodustat data were collected as previously described 17,19 and calculated via standard noncompartmental analysis with WinNonlin 6.3 or higher (Certara, Princeton, NJ). All calculations were based on actual sampling times.…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…Clinical data have shown that daprodustat administered orally is rapidly absorbed, with time to maximum concentration (t max ) of 1–4 hours, and exhibits dose‐proportional increases in exposure 15–17 . The pharmacokinetic (PK) profile of daprodustat is similar in the healthy adult and CKD populations as the maximum observed drug concentration (C max ), area under concentration‐time curve (AUC), and t max have been shown to be comparable in both groups 18 .…”
mentioning
confidence: 99%
“…16 Daprodustat C max and AUC were increased 2-fold in participants with moderate (Child-Pugh class B) hepatic impairment versus healthy controls; in participants with mild hepatic impairment, C max was comparable with controls and AUC was increased 1.5-fold. 1,17…”
Section: Pharmacokineticsmentioning
confidence: 99%